Feasibility of a Novel Sparse Orthogonal Collimator–Based Preclinical Total Marrow Irradiation for Enhanced Dosimetric Conformality - Abdelhamid, Amr M. H.; Jiang, Lu; Zuro, Darren; Liu, An; Madabushi, Srideshikan Sargur; Ghimire, Hemendra; Wong, Jeffrey Y. C.; Saldi, Simonetta; Fulcheri, Christian; Zucchetti, Claudio; Pierini, Antonio; Sheng, Ke; et al. (Frontiers in Oncology, 2022)
Total marrow irradiation (TMI) has significantly advanced radiation conditioning for hematopoietic cell transplantation (HCT) in hematologic diseases by reducing conditioning-induced toxicities and improving survival outcomes in relapsed/refractory patients. Recently, preclinical 3D image-guided TMI has been developed to enhance mechanistic understanding of the role of TMI and to support the development of experimental therapeutics. However, a comparative dosimetric analysis between preclinical and clinical TMI reveals that the preclinical TMI treatment lacks the ability to reduce the dose to some of the vital organs that are very close to the skeletal system and thus limits the ability to evaluate radiobiological relevance. To overcome this limit, we introduce a novel Sparse Orthogonal Collimators (SOC) based TMI and evaluate its ability to enhance dosimetric conformality. The SOC-TMI based dose modulation technique significantly improves TMI treatment planning by reducing radiation exposures to critical organs that are close to the skeletal system which leads to reducing the gap between clinical and preclinical TMI.